The genetic determinants of oral diseases in Africa: The gaps should be filled - Sudi, Stephen M.; Kabbashi, Salma; Roomaney, Imaan A.; Aborass, Marwa; Chetty, Manogari (Frontiers in Oral Health, 2022)
Oral diseases are a major health concern and are among the most prevalent diseases globally. This problem is becoming more prominent in the rapidly growing populations of Africa. It is well documented that Africa fosters the most diverse genetic make-up in the world. However, little work has been conducted to understand the genetic basis of oral diseases in Africans. Oral health is often neglected and receives low prioritisation from funders and governments. The genetic determinants of highly prevalent oral diseases such as dental caries and periodontal disease, and regionally prevalent conditions such as oral cancer and NOMA, are largely under-researched areas despite numerous articles alluding to a high burden of these diseases in African populations. Therefore, this review aims to shed light on the significant gaps in research on the genetic and genomic aspects of oral diseases in African populations and highlights the urgent need for evidence based dentistry, in concert with the development of the dentist/scientist workforce.